The role of contextual signal TGF-β1 inducer of epithelial mesenchymal transition in metastatic lung adenocarcinoma patients with brain metastases: an update on its pathological significance and therapeutic potential - Piña Batista, Kelvin; Piña, Kenia; Ramos, Aida; Vega, Ivan Fernandez; Saiz, Antonio; Vega, Marco (Contemporary Oncology/Współczesna Onkologia, 2019)
Lung adenocarcinoma (LA) is the most common cause of cancer-related death worldwide. Despite the advances over last decade in new targeted therapies, cancer genetics, diagnostics, staging, and surgical techniques as well as new chemotherapy and radiotherapy protocols, the death rate from LA remains high. The tumour microenvironment is composed of several cytokines, one of which is transforming growth factor b1 (TGF-β1), which modulates and mediates the expression of epithelial-mesenchymal transition (EMT), correlated with invasive growth in LAs, and exhibits its pleiotropic effects through binding to transmembrane receptors TbR-1 (also termed activin receptor-like kinases – ALKs) and TbR-2. Accordingly, there is an urgent need to elucidate the molecular mechanisms associated with the tumoural spreading process and therapeutic resistance of this serious pathology. In this review, we briefly discuss the current role of contextual signal TGF-β1 inducer of epithelial mesenchymal transition in metastatic lung adenocarcinoma patients with brain metastases, and give an overview of our current mechanistic understanding of the TGF-β1-related pathways in brain metastases progression, TGF-β1 pathway inhibitors that could be used for clinical treatment, and examination of models used to study these processes. Finally, we summarise the current progress in the therapeutic approaches targeting TGF-β1.